If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(1/3)*(y+17) = 3*y-(5*(y-3)) // - 3*y-(5*(y-3))
(1/3)*(y+17)+5*(y-3)-(3*y) = 0
(1/3)*(y+17)+5*(y-3)-3*y = 0
1/3*(y+17)+5*(y-3)-3*y = 0
1/3*(y+17)+5*(y-3)-3*y = 0
16/3*y-3*y-28/3 = 0
7/3*y-28/3 = 0
7/3*y-28/3 = 0
7/3*y-28/3 = 0 // + 28/3
7/3*y = 28/3 // : 7/3
y = 28/3/7/3
y = 4
y = 4
| 9=7c-5 | | 12x-7=4x+14 | | 5.3x+1=3.8x-11 | | 2(3x-6.5)=20 | | (3x-8)+(2x+5)-(4x-8)= | | 5/13=x/8 | | 3x+1.4=x+1.8 | | 54/x=-6 | | 6-9x=-57 | | 4-3x=-8x+14 | | 5x=x+0.8 | | 35.4=-6g | | 2(z-4)+3z=4-(z+2) | | -7v+5v=-2-8 | | 11x=60.5 | | 4-3x=8x+14 | | 7y-10-5y+5=0 | | z-5z=-4 | | -(5x+2)=8 | | -2x+15=-17 | | 4u=-7 | | 44*.5= | | 3x^2-23x+13=0 | | -(11x^2+2x-1)= | | -6+5x=2+3x-2x | | 14v-16v=40 | | (1/5)x=-14 | | X/x+2=5/4 | | 77=4x+7x | | 4t^2+28t=0 | | 81-y^2=0 | | 16x-6=36x+9 |